Targeted and immunotherapeutic strategies for castration-resistant prostate cancer: emerging strategies, challenges, and future directions - Wang, Bo; Xiang, Yuchu; Fang, Zitong; Le, Junjun; Jian, Yu; Chen, ShuLian; Li, Daobing; Liang, Guobiao; Pan, Xiaoting (Frontiers in Immunology, 2025)
Castration-resistant prostate cancer (CRPC) represents an advanced stage of prostate cancer progression. Although the combination of androgen deprivation therapy (ADT) with chemotherapy and first generation hormone therapy is initially effective, patients ultimately develop resistance. In recent years, breakthroughs in targeted therapies and immunotherapies, along with the emergence of novel combination strategies, have provided new hope for patients with CRPC. This article systematically reviews the latest advancements in targeted and immunotherapeutic approaches for CRPC, integrating clinical data and mechanistic studies to analyze the efficacy and challenges of novel agents (e.g., second-generation AR inhibitors, PARP inhibitors, PSMA-targeted therapies) and combination regimens. It also provides insights for exploring future optimization directions.